Understanding South Asian Immigrant Women's Food Choices in the Perinatal Period - Higginbottom, Gina M.A.; Vallianatos, Helen; Shankar, Janki; Davey, Christina; Osswald, Barbara (ClinMed International Library, 2016)
Background: Food practices throughout the perinatal period have a profound influence on the health and wellbeing of a mother and her child. Following migration, pregnant immigrant women bring with them culturally-situated beliefs about appropriate eating behaviours, while simultaneously encountering new socio-cultural environments that can negatively affect their food choices. Research is needed to inform and improve the provision of culturally appropriate maternal health and nutritional care. Methods: We employed a focused ethnography, photo-voice methods, and photo-assisted interviews to explore and understand South Asian immigrant women’s food choices and practices during the perinatal period and to investigate the intersectionality of these factors in a social context of cultural adaptation and adjustment. Findings: The key themes constructed from the data included (a) general health beliefs, (b) antenatal and postnatal food choices including Ayurvedic medical beliefs, (c) social advice and socio-economic factors.